2014
DOI: 10.1007/978-3-642-28554-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatical Approaches to Unstructured/Disordered Proteins and Their Interactions

Abstract: Abstract. Intrinsically unstructured/disordered proteins (IUPs/IDPs) exist as highly flexible conformational ensembles without adopting a stable three-dimensional structure. Experimental and bioinformatical studies in the past two decades have shown that these proteins play a central role in various signaling and regulatory processes. Accordingly, their frequency in higher eukaryotes reaches high proportions and their malfunction can be connected to a wide variety of diseases. Recognizing the biological import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Most disorder prediction algorithms (such as disopred, Ward et al (2004)) perform well for stable, globular domains, or highly flexible disordered regions without a strong structural preference. However, their performance does not meet expectations for structurally ambiguous regions (Mészáros et al, 2014). Therefore, in comparison to sequence-based disorder prediction algorithms, cabs-flex is better suited to detecting non-obvious dynamic behavior (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most disorder prediction algorithms (such as disopred, Ward et al (2004)) perform well for stable, globular domains, or highly flexible disordered regions without a strong structural preference. However, their performance does not meet expectations for structurally ambiguous regions (Mészáros et al, 2014). Therefore, in comparison to sequence-based disorder prediction algorithms, cabs-flex is better suited to detecting non-obvious dynamic behavior (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…The CABS-flex method provides an alternative to other efficient computational tools generating protein residue fluctuation profiles, such as sequence-based predictors of protein disordered regions (Mészáros et al , 2014) or coarse-grained normal mode analysis (NMA; Ma, 2005). Most disorder prediction algorithms [such as DISOPRED, Ward et al (2004)] perform well for stable globular domains or highly flexible disordered regions without a strong structural preference.…”
Section: Discussionmentioning
confidence: 99%
“…The high-confidence predictions of ANCHOR covering these binding regions in the Nterminal domain, Fig. 5C, is the strongest prediction-level evidence for the presence of disordered binding regions (as opposed to coiled-coil region or a short collapsed structure) [40].…”
Section: The Combined Usage Of Methods For the Disorder Disordered Bi...mentioning
confidence: 90%
“…The principles of the combined usage of different methods in the field of protein structure/function analysis are described by various authors, frequently using the example of human p53, which is one of the most complex IDPs. Comparing several disorder predictors, optimized for various typical lengths of disorder, and disordered binding region -prediction by ANCHOR, Meszaros and colleagues gave a profile of p53 disordered binding regions encompassing short linear binding motifs [40]. Huart and Hupp have shown that p53 long disordered regions were enriched in potential disorder-based binding motifs which overlap numerous sites of post-translational modifications, and suggested how amino acid modifications evolved to regulate dynamically the p53 interactome [18].…”
Section: The Combined Usage Of Methods For the Disorder Disordered Bi...mentioning
confidence: 99%
“…Thus, the exact identification of IDPs and intrinsically disordered segments is an important aspect in large-scale structure-function studies. It has recently been pointed out that some structural elements, referred to as oligomeric fibrillar motifs below, are often predicted to be disordered by current IDP prediction algorithms [ 3 , 4 ]. Although the occurrence of structured motifs within low-complexity segments and other regions regularly predicted as IDPs has been noted [ 5 ], these are rarely taken explicitly into account when evaluating IDP abundance at the proteome level.…”
Section: Introductionmentioning
confidence: 99%